Recurrent Transient Ischemic Attacks in a Patient with POEMS Syndrome. (4th March 2014) - Akyol, A.; Nazliel, B.; Batur Caglayan, H. Z.; Oner, Y.; Sucak, G. Turkoz
Abstract : A 47-year-old female with a prior history of POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes) syndrome was admitted with transient ischemic attacks complicated by dysarthria and right-sided hemiparesis. A blood survey indicated thrombocytosis and hyperfibrinogenemia while imaging of intracranial vasculature showed occlusion of the bilateral middle cerebral arteries. POEMS syndrome, of which arterial thromboses have been mentioned as a manifestation, is rarely accompanied by transient ischemic attacks. The pathophysiologic mechanism is yet unclear and needs further investigation.